Meta-analysis highlight the therapeutic potential of stem cells for premature ovarian failure - Amna Umer; Khalil Ahmad; Nasar Khan; David Lawrence Greene; Sabiha Shamim; Umm E. Habiba (Regenerative Therapy)
Stem cell (SC) transplantation has shown potential as a therapeutic approach for premature ovarian failure (POF). Despite this, no quantitative analysis has been conducted on the efficacy of SC therapy for POF in humans. To address this gap, the present study conducted a meta-analysis to evaluate the effectiveness of the transplantation of SC in improving ovarian function among POF patients. A systematic review in this regard by searching PubMed, ScienceDirect, clinicalTrial.gov, and Cochrane's library databases was conducted to identify relevant studies, while associated reviews were also considered. The extracted data included parameters such as estradiol (E2), follicle-stimulating hormone (FSH), follicle count (FC), ovarian weight (OW), number of pregnancies, and live birth. As per the combined effect taking the last follow-up time, the level of FSH and AMH for the SC group was lower than these were at the baseline as (SMD: 1.58, 95% CI: 0.76 to 3.92, P-value: 0.185 > 0.05, I2: 94.03%) and (SMD: 1.34, 95% CI: 0.77 to 1.92, P-value: 0.001 < 0.05, I2: 0%) respectively. While the means of E2 and OW for the SC group was higher than these were at the baseline as (SMD: −0.47, 95% CI: −0.73 to −0.21, P-value: 0.001 < 0.01, I2: 38.23%) and (SMD: −1.18, 95% CI: −2.62 to 0.26, P-value: 0.108 > 0.05, I2: 76.68%) respectively. The overall effect size measured with proportion of pregnancy and live birth at a 5% level of significance expected SC transplantation results were as (combined proportion: 0.09, 95% CI: 0.03 to 0.15, P-value: 0.002 < 0.05, I2: 46.29%) and (SMD: 0.09, 95% CI: 0.03 to 0.15, P-value: 0.003 < 0.05, I2: 1.76%) respectively. Based on the fixed-effects model, the estimated average log odds ratio of Follicles count was 1.0234 (95% CI: 0.1252 to 1.9216). Therefore, the average outcome differed significantly from zero (P-value: 0.0255 < 0.05) due to SC transplantation. These results suggest that using SCs to restore ovarian function may be viable for treating POF. However, larger and better-quality investigations would need to be conducted in the future due to the heterogeneity of the examined studies.